Clinical Outcomes of Implantable Collamer Lenses for the Treatment of Myopia in Eyes with Anterior Chamber Depth (<3.0 mm) at a Single Center in the United States - Hirabayashi M; Virdi G; Abramson AJ; Nasser T; Vanrachack A; Parkhurst G (Clinical Ophthalmology, 2025)
Matthew Hirabayashi,1 Gurpal Virdi,2,3 Andrew J Abramson,4 Taj Nasser,5 Anthony Vanrachack,1 Gregory Parkhurst1 1Parkhurst NuVision LASIK Eye Surgery, San Antonio, TX, USA; 2University of Missouri Columbia School of Medicine, Columbia, MO, USA; 3Mason Eye Institute, University of Missouri, Columbia, MO, USA; 4Texas State University, San Marcos, TX, USA; 5Tylock George Eye Care and Laser, Irving, TX, USACorrespondence: Matthew Hirabayashi, Parkhurst NuVision LASIK Eye Surgery, 9725 Datapoint Dr Suite 106, San Antonio, TX, 78229, USA, Tel +1 314 578 2374, Email matthewhirabayashi@gmail.comPurpose: To report the clinical outcomes of ICL implantation for the treatment of myopia in American patients at a single center with central internal anterior chamber depth (ACD) less than the FDA-approved 3.0 mm.Patients and Methods: Data was retrospectively obtained from 943 eyes of 560 patients between 4/6/2022 and 7/15/2024 which included 231 eyes of 120 patients with internal central ACD of < 3.0 mm and 712 eyes of 440 patients with internal central ACD of ≥ 3.0 mm as measured by the Pentacam AXL (OCULUS, Wetzlar, Germany). Demographics, biometry, postoperative vault, and any complications were recorded. Patients were seen 1 day, 1 month, and 2 months, and followed regularly by their primary eyecare provider with instructions to return in the event of any problems. Rates of ICL explantation were statistically compared using the Fisher’s Exact test. Postoperative vault and IOP were compared using the Student’s t-test.Results: Of the 231 eyes with ACD < 3.0 mm, 0.4% (1/231) required intraocular surgical intervention including ICL explant, exchange, or toric lens repositioning at some point in the postoperative period or were clinically judged to have a vault requiring an exchange compared to 3.7% (26/712) eyes with ACD ≥ 3.0 mm (p = 0.0103). Average postoperative vault for the eyes with ACD < 3.0 mm was 437.22 ± 191.93 microns compared to 560.73 ± 193.65 in eyes with ACD ≥ 3.0 mm (p < 0.001). IOP and visual acuity at 1 month were similar between the groups.Conclusion: Outside the US, the lower limit of ACD is 2.8 mm for myopia correction. This single center study demonstrates that ICL surgery in American eyes with ACDs < 3.0 mm may also be safe and result in excellent outcomes with comparable rates of exchange or enhancement to eyes meeting the FDA guidelines.Keywords: refractive surgery, vision correction, phakic IOLs, vault, sizing